Plasminogen activator inhibitor type 1 biosynthesis and mRNA level are increased by dexamethasone in human fibrosarcoma cells. - Andreasen, P A (1987)
Dexamethasone increases type 1 plasminogen activator inhibitor (PAI-1) activity released from the human fibrosarcoma cell line HT-1080. We demonstrated that dexamethasone caused about 10-fold increases in the intracellular and extracellular levels of PAI-1 protein, as measured by an enzyme-linked immunosorbent assay, in the rate of PAI-1 biosynthesis, and in the PAI-1 mRNA level. The effects on PAI-1 biosynthesis and mRNA level were detectable within 4 h and were maximal 16 to 24 h after the addition of dexamethasone. Cycloheximide did not inhibit the dexamethasone-induced increases in the capacity of the cells to synthesize PAI-1 and in the PAI-1 mRNA level.